Development of Animated Video Media for Civic Education Learning in Elementary Schools - Linda, Nur (Yayasan Zia Salsabila, 2024)
This study investigates the effectiveness of inquiry-based civic education media in enhancing civic literacy among elementary school students. The problem addressed is the limited engagement of students in conventional Pancasila and Civic Education (PPKn) learning, which tends to emphasize rote knowledge over critical, participatory, and reflective dimensions of citizenship. The objective of this research is to explore how inquiry-oriented learning media can foster students’ understanding, critical reasoning, and social responsibility in a contextual and meaningful way. Employing a qualitative approach, data were collected through interviews, classroom observations, and documentation in an elementary school in Kendari, Indonesia. NVivo 14 software was utilized for thematic analysis to ensure systematic and rigorous interpretation. The results reveal that the use of inquiry-based media significantly enhances students’ comprehension of civic values, promotes critical thinking, strengthens civic identity, and increases participation in school life. These findings contribute to the development of multidimensional civic literacy models and underscore the pedagogical value of inquiry strategies in primary education.